Development, Risk and Legal Aspect of Fintech, Insurtech and Proptech in Indonesia - Yunita, Irni (PT. Hafasy Dwi Nawasena, 2024)
In recent years, the development of financial technology sectors in Indonesia has garnered significant attention and influences how individuals access financial services. Therefore, there is a need for an understanding of the development, risks, and legal framework of the fintech industry. This study aims to describe developments, risks, and legal aspects of financial, Insurance and Property Technology. This study uses a descriptive analysis method and library research by collecting secondary data from articles, news and official websites to delineate the trends, risks and legal aspects of Financial, Insurance and Property Technology. The results of the study show that these three sectors have experienced significant developments in recent years. However, there are also risks such as data security risk, credit risk and legal compliance risk. Therefore, companies in the fintech, insurtech and proptech sectors need to strengthen their security and risk management systems. In the legal aspect, shows that regulations and policies in Indonesia are still quite limited and have not fully supported the development of these sectors. However, the Indonesian government has started to pay attention to this needs to develop a more comprehensive regulatory framework for these sectors. Therefore, companies need to pay attention to ensure their law’s compliance.